2015
DOI: 10.1128/aac.04842-14
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Hydroxypropyl Chitosan Nail Lacquer To Protect against Dermatophyte Nail Infection

Abstract: The development of a topical agent that would strengthen the nail, improve the natural barrier, and provide better drug penetration to the nail bed is needed. In this study, we examined the effects of a hydroxypropyl chitosan (HPCH)-based nail solution using a bovine hoof model. Following application of the nail solution, changes in the hardness of the hoof samples were measured using the Vickers method. Tensile and flexural strengths were tested by stretching or punching the samples, respectively. The ultrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…This finding is in contrast with the recommendations of experts, suggesting that the length of treatment with topical drugs in mild-to-moderate onychomycosis should not be less than 1 year. It was even suggested that an extension of the duration of treatment to 18 months could produce a better clinical outcome that reflects true nail pathology [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast with the recommendations of experts, suggesting that the length of treatment with topical drugs in mild-to-moderate onychomycosis should not be less than 1 year. It was even suggested that an extension of the duration of treatment to 18 months could produce a better clinical outcome that reflects true nail pathology [10] .…”
Section: Discussionmentioning
confidence: 99%
“…HPCH is able to form an invisible film on the nail surface, which may prevent fungal invasion [10] . Furthermore, HPCH allows the composition to remain in contact with the nail surface long enough for a substantial ciclopirox penetration into and through the nail [11] .…”
mentioning
confidence: 99%
“…This is a typical effect of hydroxypropyl chitosan, which, when applied onto the nail surface, reduces the penetration of the dermatophyte hyphae [15]. Interestingly, the effect of placebo was maintained and even increased during the follow-up, most probably due to the persistence of hydroxypropyl chitosan in the nail holes in the nails for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…The factors affecting the solvent mechanisms might include the effects of the solvent on the film formed after evaporation, the drug's affinity for the lacquer formulation, and the effect of the solvent on the nail plate. Isopropyl alcohol is commonly used in nail care to dissolve the nail keratin or to remove the solution from the nail surface (Ghannoum et al 2015), and this property might have enhanced the permeation of the drug. In addition, isopropyl alcohol facilitates the dissolution of the lipid layer of the nail plate, thereby contributing to enhancing the drug permeation (Murdan 2002).…”
Section: Discussionmentioning
confidence: 99%